Analyzing the influence of facing batter on reinforcement loads of reinforced soil walls under working stress conditions. Issue 6 (December 2022) - Wang, Chunhai; Wang, Lei; Liu, Huabei
Abstract: The level of reinforcement loads in a reinforced soil retaining wall is important to its satisfactory operation under working stress conditions since it basically determines the wall deformation. Consequently, proper estimation of the reinforcement load is a necessary step in the service limit-state design of this type of earth retaining structures. In this study, a force equilibrium approach is proposed to quantify the influence of facing batter on the reinforcement loads of reinforced soil walls under working stress conditions. The approach is then combined with a nonlinear elastic approach for GRS walls without batter to estimate the reinforcement loads neglecting toe restraint. The approximate average mobilized soil strength in the retaining wall is employed in the force equilibrium analysis. The predictions of reinforcement loads by the proposed method were compared to the experimental results from four large-scale tests. It is shown that the proposed semianalytical approach has the capacity to reproduce the reinforcement loads with acceptable accuracy. Some remaining issues are also pinpointed. Highlights: An approach is proposed to analyze the facing batter influence. It is combined with a nonlinear elastic method to analyze reinforcement load. The proposed approach is validated against the results of 4 large-scale tests.